Два світи культурної спадкоємності - Пономар, Л. (Народна творчість та етнологія, 2022)
Війна Росії проти України показала терористичне обличчя окупантів, їхні варварські «цінності», світогляд вандалів. Окупанти впроваджують стратегію знищення української ідентичності, духовної спадщини українців. Водночас героїзм українського народу в боротьбі за незалежність згуртував увесь цивілізаційний світ. Самоорганізація українців в обороні своєї землі засвідчила зрілість громадянського суспільства. Це є феноменом українського суспільства, що ставить перед науковцями важливе завдання щодо його розкриття. У статті розглядаються різні фактори, які його пояснюють. На думку авторки, в Україні на початку ХХІ ст. велике значення мали позитивні явища в розвитку народної культури, пов’язані з процесами самоідентифікації та самовизначення. Це, зокрема, виразно простежується за матеріалами вивчення відродження традиційного вбрання та поширення народного стилю в повсякденні, безпосередньо пов’язане з національним піднесенням у період Помаранчевої революції та Революції гідності. Народний одяг завжди був важливим маркером національної ідентифікації, однак у час війни 2014 року, розв’язаної Росією, використання народного вбрання стало виявом активної позиції носіїв у захисті національного суверенітету. Ці процеси показують, що для розвитку кожного суспільства одним із визначальних факторів є традиційна культура. За матеріалами інтернет-ресурсів, а також опитувань у статті розглядаються світоглядно-психологічні та ментальні характеристики росіян-окупантів та українців. Вони засвідчують наявність двох протилежних світів: світу рабів і світу вільних громадян. Акцентується значення наукових досліджень гуманітарних наук для спростування фальсифікацій путінськими політиками культурної спадщини українців, прямої спадкоємності Київської держави, безперервної традиції. The war of Russia against Ukraine has shown the terrorist face of the occupants, their barbaric values, and the worldview of the vandals. The occupants are pursuing a strategy of destruction of Ukrainian identity and the spiritual heritage of Ukrainians. At the same time, the heroism of the Ukrainian people in the struggle for independence has united the entire civilized world. The self-organization of Ukrainians in the defense of their land has assured the maturity of the civil society. This is a phenomenon of Ukrainian society, which forms an important issue for scientists to study. Various factors explaining it are considered in the article. In the authoress opinion, positive phenomena in the development of folk culture associated with the processes of self-identification and self-determination are of great importance in Ukraine at the beginning of the 21st century. In particular, it can be seen clearly after the materials of study of the revival of traditional clothing and the spread of folk style in everyday life, connected directly with the national raising during the Orange Revolution and the Revolution of Dignity. Folk clothing has always been an important marker of national identification, but during the war of 2014, started by Russia, the use of folk costumes became a manifestation of the bearers’ active stand in the national sovereignty defense. These processes show that traditional culture is one of the determining factors for the development of every society. The worldview, psychological, and mental characteristics of the Russian occupants and Ukrainians are considered after the materials of Internet resources and surveys. They confirm the existence of two opposite worlds: the world of slaves and the world of free citizens. The importance of scientific research in the humanities for the refutation of the falsifications of Ukrainian cultural heritage, the direct succession of the Kyiv state, and the continuous tradition by Putin’s politicians is emphasized.